2021
DOI: 10.3390/microorganisms9102061
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Footprints of Burkholderia Sensu Lato Rhizosphere Bacteria Active against Maize Fusarium Pathogens

Abstract: Consistent with their reported abundance in soils, several Burkholderia sensu lato strains were isolated from the rhizosphere of maize plants cultivated at different sites in central México. Comparative analysis of their 16S rRNA gene sequences permitted their separation into three distinctive clades, which were further subdivided into six other clusters by their close resemblance to (1) Trinickia dinghuensis; (2) Paraburkholderia kirstenboschensis, P. graminis, P. dilworthii and P. rhynchosiae; (3) B. gladiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 86 publications
0
3
0
1
Order By: Relevance
“…The other is that the relative abundance of some beneficial bacteria significantly increased in the soils of the TCMR treatments, including Burkholderia , Sphingobium , and Rhizobium , which were significantly negatively correlated with the abundance of Fusarium ( Figure 9 ), suggesting that they may inhibit the growth of Fusarium . Burkholderia is the most commonly reported genus of bacteria with antagonistic activity against Fusarium and inhibits Fusarium diseases in many plants, including maize, tomatoes, and bananas ( Abdel-Aziz et al., 2020 ; Barrera-Galicia et al., 2021 ). Beneficial microorganisms may shield plants from diseases by altering the plant immune system ( Liu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The other is that the relative abundance of some beneficial bacteria significantly increased in the soils of the TCMR treatments, including Burkholderia , Sphingobium , and Rhizobium , which were significantly negatively correlated with the abundance of Fusarium ( Figure 9 ), suggesting that they may inhibit the growth of Fusarium . Burkholderia is the most commonly reported genus of bacteria with antagonistic activity against Fusarium and inhibits Fusarium diseases in many plants, including maize, tomatoes, and bananas ( Abdel-Aziz et al., 2020 ; Barrera-Galicia et al., 2021 ). Beneficial microorganisms may shield plants from diseases by altering the plant immune system ( Liu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quando consideramos antagonismo dos gêneros de bactérias obtidos no presente trabalho é possível citar alguns exemplos descritos na literatura como: Burkholderia antagônica à Fusarium spp., patógeno de gramíneas (LUVIZOTTO, 2008;BARRERA-GALICIA et al 2021 1-F: floresta; 2-L: lavoura; 3-P: pecuária; 4-IPL: integração pecuária-lavoura; 5-iLP: integração lavoura-pecuária; 6-iLF: integração lavoura-floresta; 8-ILPF: lavoura e floresta por 2 anos e após pecuária e floresta por 2 anos; 9ILPF: pecuária e floresta por 2 anos e lavoura e floresta por 2 anos; 10-ILPF: integração lavoura pecuária floresta. *Similaridade.…”
Section: Discussionunclassified
“…Burkholderia arboris has been widely isolated from the rhizosphere zone of the soil, and has been shown to possess antifungal activity (Barrera-Galicia et al, 2021); however, the antifungal compound is yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Burkholderia cepacia complex (BCC) is a group of antibiotic resistant bacteria, including Burkholderia arboris , capable of producing bioactive compounds via NRPS and PKS ( Thomson and Dennis, 2012 ). Burkholderia arboris has been widely isolated from the rhizosphere zone of the soil, and has been shown to possess antifungal activity ( Barrera-Galicia et al, 2021 ); however, the antifungal compound is yet to be identified.…”
Section: Introductionmentioning
confidence: 99%